Quantifying displacement on the South Tibetan Detachment normal fault, Everest massif, and the timing of crustal thickening and uplift in the Himalaya and South Tibet - Searle, M. P.; Simpson, R. L.; Law, R. D.; Waters, D. J.; Parrish, R. R. (Journal of Nepal Geological Society, 2002)
ABSTRACT Lithospheric convergence of India and Asia since collision has resulted in horizontal shortening, crustal thickening and regional metamorphism in the Himalaya and beneath southern Tibet. The boundary between the High Himalaya and the Tibetan plateau is a large scale, north-dipping, low-angle normal fault termed the South Tibetan Detachment (STD) which was active contemporaneously with the Main Central Thrust (MCT) bounding the southern margin of the High Himalaya. Previous studies have estimated minimum northward displacement along the STD of 35 km along the Everest profile. Here, we demonstrate approximately 200 km of southward displacement of footwall sillimanite + cordierite gneisses (minimum 90-108 km), formed at 600-630°C and pressures of 4.0-4.9 kbar ( 14-18 km depth), beneath the STD which acted as a passive roof fault during southward flow of the hot, viscous, ductile middle crust. U-Th-Pb dating of gneisses, sheared and cross-cutting leucogranites indicates that ductile shearing was active at 17-16 Ma, and later brittle motion at <16 Ma cuts all rocks in the footwall. High temperatures (>620°C) were maintained for -14 Ma along the top of the High Himalayan slab from 32-18 Ma, implying active crustal thickening and high topography in south Tibet during this time. The ending of metamorphism and melting in the Himalaya and ductile shearing along the STD coincides with the initiation of strike-slip faulting in SW Tibet and E-W extension in south Tibet.